Sustainability of Local Wisdom Transferring on Lanna Food - Aromkliang, Tasanee; Chatraphorn, Suparp (Kasetsart Journal of Social Sciences, 2014)
This qualitative research was conducted to investigate 1) the history and the community context on the wisdom of local food in social dimension and Lanna tradition, 2) the development of local wisdom transferring on Lanna food, and 3) an approach on transferring and maintaining the local wisdom of Lanna food for local sustainability. The informants composed of: 1) experts and scholars on Lanna traditional arts and history, 2) food and nutrition experts, 3) a networking group of Lanna food wisdom, 4) native people, and 5) educational institutions and related organizations. Data were collected from documents, observations, interviews, and group discussions. The findings revealed that: 1) the history and the community context on the wisdom of local food in the social dimension and Lanna tradition were related to the native groups as Thailue, Thaikhern, Thaiyuan, Thailua, and Thaiyong; 2) the food concerned with the Lanna cultures and traditions, beliefs and values were Laab, Gaeng Ho, Gaeng Orm, and Gaeng Khanoon, while those concerned with Lanna history were Gaeng Hungle, Khao Soi, and Khanomjeen Num-ngeow; 3) the transferring and maintaining the local wisdom of Lanna food could be divided into 3 approaches – on cultures and traditions, on beliefs, and on method and skill. An approach on local wisdom transferring of Lanna food included 4 aspects. 1) The local wisdom experts: a database of local wisdom experts on Lanna food should be available. Besides, a provision of food activities for resource persons, communication, and honor and value of local scholars should be supported. 2) The learners: there should be reinforcement of knowledge dissemination among the local people, encouragement on awareness of the value of Lanna food, and motivation on learning. 3) The transferring process: demonstration, participation, creativity, and idea sharing are recommended. 4) The outcomes of knowledge transferring: research, conservation, and development of Lanna food wisdom are needed to be focused.